Sustainable development from an evolutionary perspective - Bas Schrauwen (The Central European Review of Economics and Management (CEREM), 2020)
Aim: awareness of the inherent unsustainability of past economic development, the magnitude and multidimensionality of the resulting environmental problems and the urgency of a paradigm shift in politics and economics. ~ Design / Research methods: reflection on Matthias Glaubrechts book "Das Ende der Evolution" (The End of Evolution). Additionally Yuval Hararis book "Sapiens" and some online sources were used. ~ Conclusions / findings: An evolutionary developed cognitive superiority has made Homo sapiens not only to the most successful but also the most destructive species ever, which makes a drastic shift towards sustainable development is overdue in the 21st century. ~ Originality / value of the article: highlighting the slow and merciless mechanisms of evolution and its big cycles, raising more awareness of the vulnerability of mankind and the necessity for a paradigm shift. ~ Implications of the research (if applicable): urgency of sustainable development in politics, economics and research.
Keywords: B52; Q01; Q59; 330; sustainable development; evolution; environmental economics; politics